British Power in the Mediterranean: Sea Protests and Notarial Practice in Nineteenth-century Malta. Issue 5 (3rd September 2022) - Pizzoni, Giada
ABSTRACT: This article investigates British presence in nineteenth-century Malta through the examination of 'sea protests': notarised documents that were produced when a ship reached port, which protected ship masters from liability for damages to ship or cargo that occurred at sea. These documents reveal some of the workings of the British Empire showing the complexity of the relationships between the Maltese and British, and the hurdles faced by the British in implementing colonial rule. This article focuses on what sea protests reveal about how the British organised legal frameworks in their colonies. It demonstrates that in Malta the British moulded local legal systems with English Common Law to suit their own ends. It further argues that the British lacked a clear vision for colonial rule in Malta beyond prioritising their military and commercial concerns, and adopted pragmatic solutions to complex issues of law, creating in the process a highly disordered legal system that was open to challenge and dispute.